2015
DOI: 10.1002/2015jb011932
|View full text |Cite
|
Sign up to set email alerts
|

Resonant ultrasound spectroscopy for materials with high damping and samples of arbitrary geometry

Abstract: Resonant ultrasound spectroscopy (RUS) is a powerful and established technique for measuring elastic constants of a material with general anisotropy. The first step of this technique consists of extracting resonance frequencies and damping from the vibrational frequency spectrum measured on a sample with free boundary conditions. An inversion technique is then used to retrieve the elastic tensor from the measured resonance frequencies. As originally developed, RUS has been mostly applicable to (i) materials wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Experiments were conducted on a cylindrical sample of Berea sandstone (Cleveland Quarries, Amherst, OH) with a diameter of 25.8 mm, a length of 305.5 mm, a mass density of 2054 kg/m 3 , and a nominal permeability ranging between 500 and 1000 mD. The linear elastic properties of this sample were characterized in previous work using resonant ultrasound spectroscopy [43]. It was found that the sample is well described by a homogeneous and isotropic material with a Young's modulus E = 9.9 GPa and a Poisson's ratio ν = 0.068.…”
Section: Experimental Arrangementmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments were conducted on a cylindrical sample of Berea sandstone (Cleveland Quarries, Amherst, OH) with a diameter of 25.8 mm, a length of 305.5 mm, a mass density of 2054 kg/m 3 , and a nominal permeability ranging between 500 and 1000 mD. The linear elastic properties of this sample were characterized in previous work using resonant ultrasound spectroscopy [43]. It was found that the sample is well described by a homogeneous and isotropic material with a Young's modulus E = 9.9 GPa and a Poisson's ratio ν = 0.068.…”
Section: Experimental Arrangementmentioning
confidence: 99%
“…10(f). For the predictions, the following parameters were used: λ = 0.73 GPa and μ = 4.64 GPa measured on this sample using resonant ultrasound spectroscopy [43], l = −1600 GPa, m = −3400 GPa, and n = −450 GPa measured by Winkler and Liu [31] on Berea sandstone using static acoustoelasticity, and α = 1600. The theoretical model captures well the features observed in experiments, except near the angle θ = 0…”
Section: A Longitudinal Motionmentioning
confidence: 99%
“…1. The linear elastic properties of this sample were characterized in previous work using resonant ultrasound spectroscopy [30]. It was found that, at the relatively low frequencies considered in this study, the sample is well described by a homogeneous and isotropic material with E ¼ 9.9 GPa and G ¼ 4.6 GPa.…”
mentioning
confidence: 99%
“…By means of the elastic constants it is possible to study the environment in which solid state phenomena occur, like e.g. phonon, electron or magnetic effects, and also probe phase transitions [2] these reasons, elastic constants provide significant information about materials and are very important in science applications, such as material science, geophysics, nondestructive testing and biomedical engineering [3]. RUS is a method for measuring elastic constants involving two steps.…”
Section: Resonant Ultrasound Spectroscopymentioning
confidence: 99%
“…The natural frequencies are classically obtained by mounting the sample with the least possible contact between a pair of piezoelectric transducers (contact RUS), one for frequency scan excitation and one for measuring the sample's response. The second step is to determine the elastic tensor from the measured resonance frequencies [3,4].…”
Section: Resonant Ultrasound Spectroscopymentioning
confidence: 99%